Research progress of Traditional Chinese and Western medicine early rehabilitation and its influencing factors in severe stroke patients (中风重症患者中西医早期康复及影响因素研究进展) - LUO Hong (罗红); YU Yanlan (余艳兰) (中西医结合护理)
Early rehabilitation of traditional Chinese and western medicine is the most effective measure to promote the rehabilitation of the body function of patients with severe stroke, which is helpful to improve the functional dysfunction of patients and improve their quality of life and quality of life. However, there are still many deficiencies in the implementation of early rehabilitation of Chinese and western medicine, which will lead to missing the best time for rehabilitation. Therefore, this paper reviewed the progress of traditional Chinese and western medicine early rehabilitation measures and influencing factors for severe stroke patients. (中西医早期康复是促进中风重症患者身体机能康复最有效的措施, 有助于改善患者的功能障碍, 提高其生存质量和生活质量。本研究对中风重症患者中西医早期康复的介入时机、方法等现状以及影响因素进行综述, 以期为中风重症患者制定、实施合理的康复护理提供参考依据。)